PENERAPAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA - Setiawan, Panji; Sudana, Dewa Nyoman (Universitas Pendidikan Ganesha, 2019)
This research was motivated by the low of mathematics learning result in 5th grade students in SD Negeri 4 Kaliuntu. The low of mathematics learning result was caused by the low understanding of the students in the subject materials presented by the teacher. In the delivery of materials, teachers did not use learning models with a scientific approach that caused students to appear less active in learning activities. The purpose of this research was to enhance the result of mathematics learning result in 5th grade students in SD Negeri 4 Kaliuntu. The kind of this research was a classroom action research wich was conducted in two cycles. Each cycle had stages including of action planning, implementation, observation, and reflection. This research used contextual teaching learning model. The results showed that there was an increase in student learning result in each cycle. Before the research was conducted, the average of students’mathematics score that taken from the first semester was 67.98. In the first cycle could be seen that there was an increase in student learning result with the average score is 78.42 and 92% classical completeness percentage. The target of research in the first cycle hadn’t reached so that the research was continued into second cycle. In the implementation of the second cycle, the deficiencies that existed in the first cycle was fixed so that the average score of students' mathematics learning result increased to 82.94 with 100% classical completeness percentage. This indicate that the target of the research has been achieved in second cycle. The average of student learning result based on the PAP is in the high category so it can be concluded that the use of contextual teahing learning model can improve the learning outcomes of 5th grade students of SD Negeri 4 Kaliuntu Year 2017/2018. Key Word: CTL, Mathematics Learning Result